Social disparities among youth and the impact on their health - Kreatsoulas, Catherine (Adolesc Health Med Ther, 2015)
PURPOSE: Social disparities among youth have been recognized as an important influence on disease risk later in the life cycle. Despite this, social problems are seldom assessed in a clinical setting. The primary objective of our study was to evaluate the impact of social disparities on the health of youth. METHODS: A self-directed, web-based screening system was used to identify social disparities along seven social domains. Participants included youth, aged 15–24 years, recruited from an urban hospital clinic. The main outcome variable, self-rated health, was captured on a 5-point Likert scale. Univariable and multivariable regression models adjusted for sex, age, and race/ethnicity were implemented to assess the association between social problems and self-rated health. Correlation between social disparity problems was estimated using phi coefficient. RESULTS: Among 383 participants, 297 (78%) reported at least one social problem. The correlation among social disparity problems was low. Social disparities had an independent effect on self-rated health, and, in a fully adjusted model, disparities in health care access and food insecurity remained significant. The presence of even one social problem was associated with a decrease in overall health (β=0.68, P<0.01). CONCLUSION: There is a high burden of social disparities among our youth urban hospital population. The presence of even one social problem increases the risk of worsening self-rated health. Evaluating the social disparities among youth in the medical setting can help elucidate factors that negatively affect patients’ health.